Study of the Peculiarities of the Product and Geographical Structure of Russia's Non-Commodity Non-Energy Exports to North African Countries - TKACHENKO M.F.; AGAPOVA A.V.; BUDARINA N.A.; KUSKOV A.N.; TATAYEVA I.Y. (Communications of International Proceedings, 2020)
The article analyzes the features of the commodity and geographical structure of Russia's non-commodity non-energy exports to the countries of North Africa. As a result of the analysis of the geographical structure of such exports, the main importer of such goods from Russia, which is Egypt, has been established. The commodity structure of non-commodity non-energy exports to North Africa has been analyzed. There is a tendency of dominance of lower-processing goods when exporting to Egypt, Libya, Morocco, Sudan, Tunisia. In the structure of exports to Algeria the higher-processing goods dominate. The main goods related to non-commodity non-energy exports exported to North Africa have been identified. The main exported lower-processing goods for all countries are fertilizers, grain, semi-finished unalloyed steel products, ammonia. However, analyzing the export of non-commodity non-energy goods from Russia on the whole, as well as the share of Russia's exports to each North African country, it was concluded that the volumes of such exports from Russia are insignificant.